2019
DOI: 10.3390/coatings9120864
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Exterior Coatings Applied to Oak Wood as a Function of Natural and Artificial Weathering Exposure

Abstract: Artificial weathering can significantly reduce the testing time needed for proving coating durability, nevertheless its reliability is still not thoroughly proven. In this study, eight different transparent and pigmented coating systems, namely oil, acrylate, alkyd and urethane alkyd were evaluated through natural and artificial weathering tests on oak samples by measuring colour, gloss and surface wettability and by macroscopic and microscopic evaluation. The oil coatings performed well in wood colour stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Therefore, lignin application on coated wood affects its original colour, but this permits additional wood protection against UV light as lignin acts as UV absorber (Teaca et al 2019). Hence, according to Ozgenç et al (2020), lignin can provide colour stabilization when a waterborne acrylic coating is applied in outdoor condition, because transparent coatings require more frequent maintenance than pigmented coatings, as UV light penetrates and degrades the film layer and decomposes the wood underneath (Oberhofnerová et al 2019).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Therefore, lignin application on coated wood affects its original colour, but this permits additional wood protection against UV light as lignin acts as UV absorber (Teaca et al 2019). Hence, according to Ozgenç et al (2020), lignin can provide colour stabilization when a waterborne acrylic coating is applied in outdoor condition, because transparent coatings require more frequent maintenance than pigmented coatings, as UV light penetrates and degrades the film layer and decomposes the wood underneath (Oberhofnerová et al 2019).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Spectroscopic techniques such as Fourier Transform Infrared Spectroscopy (FTIR) [15,16], Fourier Transform Infrared Spectroscopy-Attenuated Total Reflectance (FTIR-ATR) [17], and/or Fourier Transform Near Infrared Spectroscopy (FT-NIR) [18][19][20] are often used to investigate changes in functional groups of wood chemical components. Other aspects frequently assessed while evaluating the weathering process of materials include the determination of the surface roughness [21,22], wettability [23,24], or glossiness [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The early effects of weathering do not usually cause structural issues; rather most short-term weather results in a decline of the aesthetic attributes of wood surfaces that likely influenced the specification of wood in the first place. On uncoated surfaces or for surfaces where the coating has failed, the process of surface degradation generally begins Coatings have been the subject of considerable research [2,8,9,[11][12][13][14]. Most studies have evaluated generic finishes or have not identified brand names.…”
Section: Introductionmentioning
confidence: 99%